Peningkatan Hasil Belajar Bahasa Indonesia melalui Penerapan Metode Inkuiri Siswa SMPN 1 Sukamulia Semester Ganjil - Isnaeni, Nurul (TSAQOFAH, 2021)
Learning approach with "Application of Inquiry Method in Improving Learning Outcomes." is a learning concept that helps teachers relate the material being taught to students' real-world situations and encourages students to make connections between their knowledge and its application in their lives as family and community members. With this concept, learning outcomes are expected to be more meaningful for students. The learning process takes place naturally in the form of student activities working and experiencing, not transferring knowledge from teacher to student. A learning strategy is far more important than a result. The purpose of this classroom action research (CAR) is to find out the extent to which the learning outcomes of news text material in class VII-A students of Indonesian language lessons improve by applying the Inquiry Method. In this classroom action research (CAR) was conducted in 2 cycles, from the results of the actions taken proved to be able to improve student learning outcomes by achieving the ideal standard. From 70% in the first cycle, it can increase in the second cycle to 100%. The results of this action research indicate that the application of learning with the Inquiry Method can improve student learning mastery in Indonesian lessons with completeness reaching 100%.